Impact of Donation Frequency on Iron Stores and Hemoglobin Levels in Regular Blood Donors - Lili Novri Yanti; Rofinda, Zelly Dia; Syofiati; Rikarni; Husni; Elfira Yusri (HM Publisher, 2025)
Background: Regular blood donation, while crucial for healthcare systems, can lead to iron deficiency and anemia in donors. This study investigated the impact of donation frequency on iron stores and hemoglobin levels in regular blood donors. Methods: A cross-sectional study was conducted on 82 regular blood donors at the blood transfusion unit of Dr. M. Djamil General Hospital from February to April 2024. Participants underwent pre-transfusion screening, including a questionnaire on donation frequency and iron supplement use. Blood samples were collected during donation, and serum ferritin, hemoglobin, and erythrocyte indices (MCV, MCH, MCHC) were measured if the C-reactive protein (CRP) test was negative. Data were analyzed using the Kruskal-Wallis test. Results: The mean age of the donors was 31 years, with the majority being female (56.1%). The most common donation frequency was 6-10 times (34.15%). None of the donors reported using iron supplements. Serum ferritin levels showed significant differences among female donors based on donation frequency (p=0.004) but not among male donors (p=0.114). Hemoglobin levels also differed significantly among female donors (p=0.002), but not among male donors (p=0.213). Significant differences were observed in MCV and MCH values in both male and female donors (p<0.001 and p=0.001, respectively), but not in MCHC values (p=0.135). Conclusion: Donation frequency significantly impacts iron stores and hemoglobin levels in female blood donors but not in male donors. Regular monitoring of iron stores, particularly in female donors, is crucial to prevent iron deficiency and anemia.